Biocompatible Fluorescent Core-Shell Nanoconjugates Based on Chitosan/Bi(2)S(3) Quantum Dots - Ramanery, Fábio P. (Nanoscale Res Lett, 2016)
Bismuth sulfide (Bi(2)S(3)) is a narrow-bandgap semiconductor that is an interesting candidate for fluorescent biomarkers, thermoelectrics, photocatalysts, and photovoltaics. This study reports the synthesis and characterization of novel Bi(2)S(3) quantum dots (QDs) functionalized using chitosan (CHI) as the capping ligands via aqueous “green” route at room temperature and ambient pressure. Transmission electron microscopy (TEM), UV-visible (UV-vis) spectroscopy, photoluminescence (PL) spectroscopy, dynamic light scattering (DLS), and zeta potential (ZP) analysis were used to characterize the hybrids made of biopolymer-functionalized Bi(2)S(3) semiconductor nanocrystals. The results demonstrated that the CHI ligand was effective at nucleating and controlling the growth of water-soluble colloidal Bi(2)S(3) nanoparticles. The average sizes of the Bi(2)S(3) nanoparticles were significantly affected by the molar ratio of the precursors but less dependent on the pH of the aqueous media, leading to the formation of nanocrystals with average diameters varying from 4.2 to 6.7 nm. These surface-modified Bi(2)S(3) nanocrystals with CHI exhibited photoluminescence in the visible spectral region. Moreover, the results of in vitro MTT (3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide) assay with human osteosarcoma cells (SAOS) cell line demonstrated no cytotoxic response of the nanoconjugates. Furthermore, the results indicated that the Bi(2)S(3) QD–CHI nanoconjugates showed HEK293T cell uptake; therefore, they can be potentially used as novel fluorescent nanoprobes for the in vitro bioimaging of cells in biomedical applications. [Figure: see text]